1983
DOI: 10.1159/000260732
|View full text |Cite
|
Sign up to set email alerts
|

Monofluorophosphate Utilization in Oral Preparations: Laboratory Observations

Abstract: The major use of sodium monofluorophosphate (MFP) in oral preparations is in dentifrices. Some MFP has been used or evaluated in prophylactic pastes, occlusal sealants, dental cements and mouthrinses. In laboratory experiments, MFP has been found to reduce enamel solubility and deposit fluoride in enamel. Although fluoride uptake by enamel from MFP is less than from NaF in vitro in relatively short-term animal experiments, other evidence suggests it is the same as NaF over a longer treatment period in vivo. MF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…1, 3) is relevant and it is noteworthly that when the total fluoride content of the NaMFP samples is considered, only the post-rinse NaF 120-min plaque fluid values are statistically greater than the corresponding NaMFP values. Although the second mechanism is usually considered with respect to the calcium and phosphate content of the dentifrice abrasive [Mellberg, 1983;DePaola, 1993;Sullivan et al, 1997], a more important consideration may be the interaction between MFP and the high concentrations of calcium and phosphate present in the oral environment and more particularly where this interaction occurs. Specifically, following a NaMFP rinse, the interaction of these ions with the fluoride ion, which causes the formation of CaF 2 or fluorapatite precipitates, would only occur after MFP hydrolysis within the plaque or in the enamel pores where such mineral phases would be of maximum benefit.…”
Section: Discussionmentioning
confidence: 99%
“…1, 3) is relevant and it is noteworthly that when the total fluoride content of the NaMFP samples is considered, only the post-rinse NaF 120-min plaque fluid values are statistically greater than the corresponding NaMFP values. Although the second mechanism is usually considered with respect to the calcium and phosphate content of the dentifrice abrasive [Mellberg, 1983;DePaola, 1993;Sullivan et al, 1997], a more important consideration may be the interaction between MFP and the high concentrations of calcium and phosphate present in the oral environment and more particularly where this interaction occurs. Specifically, following a NaMFP rinse, the interaction of these ions with the fluoride ion, which causes the formation of CaF 2 or fluorapatite precipitates, would only occur after MFP hydrolysis within the plaque or in the enamel pores where such mineral phases would be of maximum benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Mellberg and Chomicki [1983] have reported similar flu oride uptakes by artificial carious lesions in vivo from a NaF dentifrice compared to a NaoPO^F dentifrice. Mellberg [1983] fur ther argues that when fluoride uptake experiments are conducted in vivo, realis tically duplicating the conditions under which the products are used, NaF and NaiPOjF should deposit similar amounts of fluoride into demineralized enamel since a large part of the Na2PC>3F is rap idly hydrolyzed to ionic fluoride by phos phatases present in the mouth. Forward [1980] has observed that the effect of fluo ride on the acid dissolution rate of enamel is related to the logarithm of the fluoride ion concentration.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent investigations revealed that demineralized enamel takes up more fluoride from MFP preparations than does sound enamel (Mellberg, 1980;Klimek, 1981). Increased F-uptake by demineralized enamel or hydrolysis of MFP by plaque bacteria may be the possible reasons for the fact that MFP is equally as effective as other fluorides in preventing dental caries (Mellberg, 1983).…”
mentioning
confidence: 99%